Elution of High-affinity (>10(-9) K(D)) Antibodies from Tissue Sections: Clues to the Molecular Mechanism and Use in Sequential Immunostaining - Gendusa, Rossella (SAGE Publications, 2014)
Inconsistent results obtained with published methods for the elution of antibodies from tissue sections prompted the assessment of both old and new methods in combination with monoclonal rabbit antibodies of known, increased affinity (above 1×10(-9) K(D)). We tested an acidic (pH 2) glycine buffer, a 6 M urea hot buffer and a 2-Mercaptoethanol, SDS buffer (2-ME/SDS). Some antibodies were not removed by the glycine pH 2 or 6 M urea hot buffers, indicating that antibodies survive much harsher conditions than previously believed. We found that the elution is dependent upon the antibody affinity and is reduced by species-specific crosslinking via a dimeric or Fab fragments of a secondary antibody. The high affinity bond of exogenous streptavidin with the endogenous biotin can be removed by 6 M urea but not by the other buffers. 2-ME/SDS buffer is superior to glycine pH 2 and 6 M urea hot elution buffers for all antibodies because of its irreversible effect on the structure of the antibodies. It also has a mild retrieving effect on some antigens present on routinely treated sections and no detrimental effect on the immunoreactivity of the tissue. Therefore, 2-ME/SDS buffer is the method of choice to perform multiple rounds of immunostaining on a single routine section.